2019
DOI: 10.1108/prr-03-2019-0006
|View full text |Cite
|
Sign up to set email alerts
|

Security perception in the adoption of mobile payment and the moderating effect of gender

Abstract: Purpose The mobile payment system has changed payment patterns and has the potential to improve people’s quality of life and increase the bank’s efficiency. In return, the risks and trust factors inevitably led to increased challenges and become a major concern in the adoption of mobile payment service. Yet, little is known about how risk and trust factors can affect the adoption of mobile payment. Hence, this paper aims to come into contact to solve these issues in the context. Design/methodology/approach A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 35 publications
3
37
1
2
Order By: Relevance
“…To feel secure while conducting financial transactions with mobile technologies it is important to minimize the concerns around the use of technology for mobile payments [35,52]. Users are concerned about the security of their payments because of viruses, which reduce their trust in mobile payments and thus can affect their usage behaviors and intentions [13]. E-commerce researchers found that users holding devices with high security related to technology are likely to adopt e-banking systems and use e-commerce platforms [12].…”
Section: Security Of Mobile Payment Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…To feel secure while conducting financial transactions with mobile technologies it is important to minimize the concerns around the use of technology for mobile payments [35,52]. Users are concerned about the security of their payments because of viruses, which reduce their trust in mobile payments and thus can affect their usage behaviors and intentions [13]. E-commerce researchers found that users holding devices with high security related to technology are likely to adopt e-banking systems and use e-commerce platforms [12].…”
Section: Security Of Mobile Payment Servicesmentioning
confidence: 99%
“…The technology acceptance model (TAM) [8], the unified theory of acceptance and use of technology (UTAUT) model [9], and the diffusion of innovations (DOI) model were used as theoretical frameworks in the context of mobile payment adoption. In the research stream, despite there being many scholars that have called for the provision of security to service providers and users within the MPS context [10][11][12][13][14][15], the relationship between users distinct perception of security and MPS success determinants such as convenience, interoperability, and trust are yet to be examined.…”
Section: Introductionmentioning
confidence: 99%
“…(Arain et al, 2019)found that consumers are associate with family friends influence them to use the technology, (Davis et al, 1989;Venkatesh et al, 2003;Yuan et al, 2005) (Kang, 2018)mobile wallet security is sensitive information of the user is not exposed to malicious attackers, mobile payment services must be constructed securely in terms of both HW and SW, and even if multiple payments. (Yang et al, 2015) different perceived risk dimensions that hinder mobile payment (m-payment) acceptance, and the risks and trust factors inevitably led to increased challenges and become a major concern in the adoption of mobile payment service and security (Hossain, 2019;Isaac & Zeadally, 2014;Wang et al, 2016).It also found three security threats, like malware, SSL/TLS vulnerabilities, and data breaches, and four security challenges, i.e., malware detection, multi-factor authentication, data breach prevention, and fraud detection and prevention in mobile payment systems (Godbole & Pais, 2008;Pasquet et al, 2008). (Hashemi & Soroush, 2006)the proposed technique is independent of security measures and the systems inside banks and financial institutions.…”
Section: Technology Factorsmentioning
confidence: 99%
“…the risk and trust factors can affect the adoption of mobile payment (Sivathanu, 2019). A research model that reflects customer satisfaction and loyalty to the adoption of mobile payment services (Hossain, 2019). (Deeparani & Jeya Prabha, 2018)The mobile financial market in India is flourishing with innovative products that provide instant cash transactions through innovative technologies that will be user-friendly and economical and hassle-free.…”
Section: Technology Factorsmentioning
confidence: 99%
“…Muslim women attach importance to visual appeal as entertainment when accessing mobile commerce [5,10,53,13,[46][47][48][49][50][51][52]. Muslim women make security a reason to be careful in online shopping and switch to other applications if they feel mobile commerce is unsafe, such as research by Blut [3,10,[54][55][56][57]. Security plays a positive relationship in Muslim women's satisfaction.…”
Section: Hypotheses Developmentmentioning
confidence: 99%